Electronic invoicing and the implications of its implementation in Colombia. Case study: José María Córdova Cadet Military School (2021)
In this document written as an essay, an approach is made around the conceptual and practical reality of electronic invoicing in Colombia. To this end, the normative evolution of the regulations to article 616-1 of the National Tax Statute is exhibited in a descriptive way, where the conceptual interpretation of electronic invoicing is recorded, identifying the evolution from conception as a document equivalent to the invoice until its issuance becomes mandatory and be the only one as a valid document in economic transactions. In addition, this essay aims to identify the regulatory evolution that has allowed the implementation of electronic invoicing, carrying out an analysis of the implementation process within the Military School of Cadets "José María Córdova" (ESMIC), describing the implications and advantages of its use. Finally, the importance for institutional efficiency that the implementation of electronic invoicing brings is raised.